A guided and unguided internet- and mobile-based intervention for chronic pain: health economic evaluation alongside a randomised controlled trial. Issue 4 (9th April 2019) - Paganini, Sarah; Lin, Jiaxi; Kählke, Fanny; Buntrock, Claudia; Leiding, Delia; Ebert, David D; Baumeister, Harald
Abstract : Objective: This study aims at evaluating the cost-effectiveness and cost-utility of a guided and unguided internet-based intervention for chronic pain patients (ACTonPainguided and ACTonPainunguided ) compared with a waitlist control group (CG) as well as the comparative cost-effectiveness of the guided and the unguided version. Design: This is a health economic evaluation alongside a three-arm randomised controlled trial from a societal perspective. Assessments were conducted at baseline, 9 weeks and 6 months after randomisation. Setting: Participants were recruited through online and offline strategies and in collaboration with a health insurance company. Participants: 302 adults (≥18 years, pain for at least 6 months) were randomly allocated to one of the three groups (ACTonPainguided, ACTonPainunguided, CG). Interventions: ACTonPain consists of seven modules and is based on Acceptance and Commitment Therapy. ACTonPainguided and ACTonPainunguided only differ in provision of human support. Primary and secondary outcome measures: Main outcomes of the cost-effectiveness and the cost-utility analyses were meaningful change in pain interference (treatment response) and quality-adjusted life years (QALYs), respectively. Economic evaluation estimates were the incremental cost-effectiveness and cost-utility ratio (ICER/ICUR). Results: At 6-month follow-up, treatment response and QALYs were highest in ACTonPainguided (44% and 0.280; mean costs = €6, 945), followed by ACTonPainunguided (28% and 0.266; mean costs = €6, 560) and the CG (16% and 0.244; mean costs = €6, 908). ACTonPainguided vs CG revealed an ICER of €45 and an ICUR of €604.ACTonPainunguided dominated CG. At a willingness-to-pay of €0 the probability of being cost-effective was 50% for ACTonPainguided (vs CG, for both treatment response and QALY gained) and 67% for ACTonPainunguided (vs CG, for both treatment response and QALY gained). These probabilities rose to 95% when society's willingness-to-pay is €91, 000 (ACTonPainguided ) and €127, 000 (ACTonPainunguided ) per QALY gained. ACTonPainguided vs ACTonPainunguided revealed an ICER of €2, 374 and an ICUR of €45, 993. Conclusions: Depending on society's willingness-to-pay, ACTonPain is a potentially cost-effective adjunct to established pain treatment. ACTonPainunguided (vs CG) revealed lower costs at better health outcomes. However, uncertainty has to be considered. Direct comparison of the two interventions does not indicate a preference for ACTonPainguided . Trial registration number: DRKS00006183.